HuARdb: human Antigen Receptor database for interactive clonotype-transcriptome analysis at the single-cell level. Issue Volume 50:Issue D1(2022) (4th October 2021) - Wu, Lize; Xue, Ziwei; Jin, Siqian; Zhang, Jinchun; Guo, Yixin; Bai, Yadan; Jin, Xuexiao; Wang, Chaochen; Wang, Lie; Liu, Zuozhu; Wang, James Q; Lu, Linrong; et al.
Abstract: T-cell receptors (TCRs) and B-cell receptors (BCRs) are critical in recognizing antigens and activating the adaptive immune response. Stochastic V(D)J recombination generates massive TCR/BCR repertoire diversity. Single-cell immune profiling with transcriptome analysis allows the high-throughput study of individual TCR/BCR clonotypes and functions under both normal and pathological settings. However, a comprehensive database linking these data is not yet readily available. Here, we present the human Antigen Receptor database (huARdb), a large-scale human single-cell immune profiling database that contains 444 794 high confidence T or B cells (hcT/B cells) with full-length TCR/BCR sequence and transcriptomes from 215 datasets. All datasets were processed in a uniform workflow, including sequence alignment, cell subtype prediction, unsupervised cell clustering, and clonotype definition. We also developed a multi-functional and user-friendly web interface that provides interactive visualization modules for biologists to analyze the transcriptome and TCR/BCR features at the single-cell level. HuARdb is freely available at https://huarc.net/database with functions for data querying, browsing, downloading, and depositing. In conclusion, huARdb is a comprehensive and multi-perspective atlas for human antigen receptors.